Endoneurial immune interplay in peripheral nerve repair: insights and implications for future therapeutic interventions - Alina Sprenger-Svačina; Alina Sprenger-Svačina; Martin K. R. Svačina; Martin K. R. Svačina; Husniye G. Otlu; Husniye G. Otlu; Tong Gao; Kazim A. Sheikh; Gang Zhang (Frontiers in Neuroscience)
The mechanisms underlying axonal injury and repair in peripheral nerves, whether due to traumatic damage or autoimmune neuropathies, are complex and not yet fully understood. Recent research indicates that an orchestrated interplay between damaged neurons, Schwann cells, and especially endoneurial immune cells such as macrophages or T cells is crucial to achieve satisfactory nerve recovery. Following axonal injury, degenerating axons and reactive Schwann cells release chemoattractants and cytokines that recruit immune cells into the endoneurium. Among them, macrophages play a pivotal role by clearing axonal and myelin debris and subsequently creating a pro-regenerative microenvironment that supports axonal outgrowth. There is evidence that the timely switch of a pro-inflammatory M1 toward a pro-regenerative M2 macrophage polarization state is crucial for satisfactory nerve recovery, and supportive cellular and humoral factors that influence the endoneurial microenvironment, such as T cells and their cytokines, can substantially impact this fragile recovery process. The latter explains the limited nerve recovery in immune neuropathies, where a pathologic pro-inflammatory shift within the endoneurial immune cell signature hampers axonal outgrowth. This review aims to provide insights into cellular and humoral determinants of the endoneurial microenvironment during nerve damage and repair, which are assumed to hold substantial potential for future therapeutic interventions, especially since current strategies to enhance peripheral nerve recovery are limited to either surgical interventions in traumatic neuropathies or immunomodulatory drugs in immune neuropathies that often fail to achieve satisfactory functional results.